Analysis of the Implementation of the Independent Learning Curriculum in Improving the Quality of Education in State Kindergartens in West Aceh Regency - Lina, Mailan; Musdiani, Musdiani; Akmaluddin, Akmaluddin (Dinasti Research, 2025)
This study aims to analyze the implementation of the independent learning curriculum in improving the quality of education in State Kindergartens in West Aceh Regency.The approach in this study is a qualitative descriptive approach with a descriptive research type. Implementation of the independent curriculum in the West Aceh State Kindergarten in improving the quality of education, namely schools planning the availability of resources, educators and staff, teaching materials and learning materials, infrastructure and facilities, technology and teaching devices, budgets, participation of parents and the community, conducting evaluations and monitoring, building cooperation with various related parties, establishing communication and stakeholder involvement. The implementation of the independent curriculum in the West Aceh State Kindergarten is by implementing a clear vision and commitment, a program for developing plans and strategies, teacher training and development programs, monitoring and evaluation, emotional support and motivation to teachers and staff, involving parents and the community, problem solving, informative and open decision making